The Importance of Understanding Nutrition and 1000 HPK in Preventing Stunting in AUD - Melisa Agustin; Raisha Chana Nurhaliza; Sita Tahera; Suci Utami Putri (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Among the various diseases and nutritional problems that young children are susceptible to, one of them is Stunting. The National Movement to accelerate nutritional improvements or more commonly known as the First 1000 Days of Life (HPK) Movement is a global movement as an effort to prevent malnutrition. The purpose of this article is to provide information and understanding about the need for prevention and early intervention. The research results show that the 1000 HPK Program implemented in Indonesia has played a very big role in reducing stunting, where the stunting rate in Indonesia was initially at 24.4% in 2021 and decreased to 21.6% in 2023 (Kemenkes. 2023 ). This research uses a qualitative method with a literature.